Determinants of equality, diversity and inclusion practices in Johor Bahru's manufacturing companies - Bathumalai, Vijaya Kumar (2024)
Many manufacturing companies in Johor Bahru face challenges in terms of Equality, Diversity and Inclusion (EDI) practices as it navigates global expansion. Challenges persisted despite efforts to enhance diversity initiatives due to embedded prejudices, limited accountability and inadequate support from the management. There are many challenges in terms of age diversity, cross cultural, inclusive leadership and language barrier. Many organisations are largely relying on foreign workers and lack of diverse representation in leadership roles underscore the pressing need for proactive strategies to adopt inclusivity. This study aims to find out on the obstacles through surveys conducted in an organisation which offers insights to highlight the effective EDI initiatives and to promote sustainable organisational growth. This study examines the impact of EDI practices at Zara Foodstuff Industries Sdn Bhd in Johor Bahru in terms of age diversity, cross-cultural, inclusive leadership and language barrier as independent variable while EDI practices at organisation at dependent variable. A total of 191 responses were collected from the selected organisation ranging from general worker up to the managerial level. Data collected is analysed by the Statistical Package for the Social Sciences (SPSS) version 26. This study found that only one hypothesis is not significant in the EDI practices at the selected organisation. Inclusive leadership is vital for fostering a supportive culture in the organisation for diversity and inclusion. Addressing language barrier is important and this can do through various method such as training. Therefore, this study will serve as a guidance to this organisation in addressing the EDI practices at workplace